밀양시 농업·농촌 발전계획 수립 연구 - 유승우 (한국농촌경제연구원, 2004)
ABSTRACT Worldly changes in agricultural policies of various countries have impacted on domestic and local agriculture and agricultural policy. Among the changes are the completion of UR negotiation in 1993, agricultural and marketing openness by the WTO/DDA agricultural negotiation, the completion of FTA between Korea and Chile, the China's participation in WTO, agricultural policy changes of many countries towards putting more emphases on multifunctionality of agriculture, and so on. Domestically, there emerge differentiations in the quality of life, competitive capacity of each products, and income level among farm households based on interests in regional agriculture and investment by the local government. So, it becomes more and more important that the local government establish regional agricultural plans. In particular, differentiation strategies which utilize local characteristics in agriculture are adopted by many local governments. Competitions among production regions become severer by branding of local products, promotion of C.I. businesses to create local image or the efforts of each local area to find export markets. In such situation, this research set up a comprehensive agricultural and rural development plan of the city of Miryang, encompassing urban and rural areas, on the basis of the understanding of regional, environmental and social-economic features of both the city as a whole and each local area and the appraisal of SWOT and potential of regional agriculture. This especially focused on the planning for local development and the identification and development of a certain specialized products. In doing so, it provided the future of agriculture and rural areas of the City of Miryang, which was based on setting up the agricultural and rural vision of the city in 21C, determining the priorities of public investment and establishing development strategy in detail. This research established the Miryang development strategy, dividing it into four areas: i) Eastern mountainous area; ii) Central and Northern semi-mountainous area; iii) Western semi-mountainous area; and vi) Southern plain area. Eastern mountainous area includes Sannae-Myon and Danjang-Myon in the administrative districts. In this area, it is planned that rural tourism areas, medical herbs areas nearby Jaeyak mountain are created, and that apple and date are selected and developed as specialized local products. Sannae-Myon would promote interchange with urban regions based on businesses about rural tourism and participating in harvesting and assist an apple festival to sustain the reputation of the region for the specialized apple. In Danjang-Myon, it planned that rural tourist facilities are improved and that amenity is valorized by the ownership on terraced farmland and a locust festival. Central and Northern semi-mountainous area covers Sanyoe-Myon, Sangdong-Myon, Bubuk-Myon and the city center of Miryang. It will develop a garden city, create a horticulture area along Miryang river and assist the production of sesame leaves as a specialized product. In addition, it will establish a large scale equestrian area and use the existing Miryang Play Area for a cultural festival. Western semi-mountainous area includes Cheongdo-Myon, Mooahan-Myon and Chodong-Myon. The development plan would promote several estates for equipped horticultural products, processing of agricultural products and animal breedings, and some special types of chilli are development as local specific products. Buddhism tourist facilities are also enhanced. Southern plain comprises of Samrangjin-Eup, Hanam-Eup and Sangnap-Myon and will be developed as a large scale rice farming area. It also develop a large scale distribution center. Strawberry and persimmon will be developed as specialised products of the regions. In addition, an area for environmentally friendly farming will be created near Hanam-Eup and Namjeon-Ri. The locally produced hops are sold to a factory for beer production. Researchers: Seung-Woo Ryu, Soo-Suk Kim, Byung-Yul Kim, Mi-Ryung Song, Kyong-Cheol Park E-mail Address: sewryu@krei.re.kr
Keywords: 밀양